Cholelithiasis in an intrahepatic gallbladder - G., Chandrasekar; Nagappa, Vivek (International Surgery Journal, 2017)
Intrahepatic gall bladder (GB) is an uncommonly encountered condition in clinical practice characterized by ectopic location of GB within the hepatic parenchyma. This condition not only produces difficulty in clinical diagnosis of various GB diseases especially cholecystitis and carcinoma but also in their management including cholecystectomy. An ectopic partial intrahepatic GB can make cholecystectomy hazardous, when indicated. A case of cholelithiasis in an intrahepatic gallbladder with concurrent choledocholithiasis is reported. The patient initially presented with pain over the right upper abdomen. The diagnosis was made during intraoperative laparoscopic cholecystectomy. This article discusses about difficultly faced during cholecystectomy and rarity of the presentation.